2018
DOI: 10.3390/molecules23051226
|View full text |Cite
|
Sign up to set email alerts
|

Nutraceuticals in Periodontal Health: A Systematic Review on the Role of Vitamins in Periodontal Health Maintenance

Abstract: Periodontal disease, a relevant public health problem worldwide, is generally considered a common pathology of elderly people. In this respect, there is agreement about that nutritional status may be a modifying factor in the progression and healing of the periodontal tissues. Vitamins have been recommended as nutraceuticals for prevention and treatment of some pathological conditions, such as cardiovascular diseases, obesity or cancer. Thus, a systematic approach to determining how the different vitamin type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 80 publications
0
58
0
4
Order By: Relevance
“…Literature review articles addressing the association of periodontitis with various nutrients, including vitamin C have been published [44][45][46]. To the best of our knowledge, this is the first systematic review that overviews findings and critically appraise the quality of studies addressing the relationship between vitamin C and periodontal disease.…”
Section: Discussionmentioning
confidence: 99%
“…Literature review articles addressing the association of periodontitis with various nutrients, including vitamin C have been published [44][45][46]. To the best of our knowledge, this is the first systematic review that overviews findings and critically appraise the quality of studies addressing the relationship between vitamin C and periodontal disease.…”
Section: Discussionmentioning
confidence: 99%
“…PD is caused by specific oral microorganisms, such as Porphyromonas gingivalis, Treponema denticola, Tannerella forsythia and Aggregatibacter actinomycetemcomitans [6][7][8], inducing loss of periodontal ligament and alveolar bone, also representing the primary cause of tooth loss [9]. Periodontal impairment is influenced by many risk factors, including alcohol, stress, smoking, heredity, DM and endocrinological changes (pregnancy or menopause); thus, maintaining periodontal health becomes a real challenge [10]. The human oral microbiome is important in the pathogenesis of PD, nutrition being a significant aspect in promoting periodontal homeostasis through antioxidant and immunomodulatory effects on bone metabolism [10][11][12].…”
Section: Diabetes Mellitus Periodontal Disease and Their Interactionmentioning
confidence: 99%
“…Periodontal impairment is influenced by many risk factors, including alcohol, stress, smoking, heredity, DM and endocrinological changes (pregnancy or menopause); thus, maintaining periodontal health becomes a real challenge [10]. The human oral microbiome is important in the pathogenesis of PD, nutrition being a significant aspect in promoting periodontal homeostasis through antioxidant and immunomodulatory effects on bone metabolism [10][11][12].…”
Section: Diabetes Mellitus Periodontal Disease and Their Interactionmentioning
confidence: 99%
“…2,3 Recently, it has been suggested that diet plays a role in maintaining periodontal health. 4,5 Recent studies suggest that low intake of some nutrients, such as vitamins, [6][7][8] omega-3 polyunsaturated fatty acids, [9][10][11] antioxidants, 12 other micronutrients, 6,8 dietary fibre, 13 high intake of saturated fats, 14 and added sugars, 15 is associated with poor periodontal condition. In addition to single foods or nutrients, nutritional research has recently focused also on the whole diet.…”
Section: Introductionmentioning
confidence: 99%